Toward a Sustainable Rural Tourism Workforce: Current Trends and Future Prospects in Indonesia - Abdullah, Dahlan; Widjaja, Herry Rachmat; Kalsum, ER. Ummi (Politeknik Pariwisata Makassar, Indonesia, 2025)
This study explores the evolving dynamics of Indonesia’s rural tourism workforce, emphasizing its role in regional development and the challenges it faces. As rural tourism grows, driven by unique cultural and natural assets, it creates employment but also exposes workforce limitations, including low digital literacy, seasonal jobs, and skill gaps. The study aims to understand how demographic factors such as age, gender, education, and skills shape the workforce and influence its adaptability. Using a qualitative descriptive approach supported by secondary data analysis, this paper examines trends in workforce composition and the impact of digital transformation on rural employment. Findings indicate a growing demand for digital competencies, yet rural areas often lack training access and strategic workforce development. Challenges like job insecurity and limited career pathways further hinder sustainable growth. The study highlights the need for targeted interventions through human resource development, emphasizing collaboration between government, educational institutions, and industry. It concludes by recommending strategic training programs, strengthened academia-industry partnerships, and policy support to ensure workforce resilience and competitiveness. This research contributes to the discourse on sustainable tourism by offering insights into workforce readiness, serving as a roadmap for strengthening Indonesia’s rural tourism sector.